Analisis Good Corporate Governance terhadap Penghindaran Pajak (Tax Avoidance) - Hermaya Ompusunggu; Afdal Afdal; Maya Richmayati (Politeknik Ganesha Medan, 2025)
This study is to analyze corporate good governance on tax avoidance in consumer good companies listed on the IDX for the period 2018-2022. The sample technique in this study used purposive sampling. Data collection techniques in this study using documentation techniques by documenting the annual reports of consumer goods and beverage manufacturing companies from 2018-2022. The method of data by conducting descriptive analysis, classical assumption test and the last is the t test and f test to see the results of this study. The results of this study are institutional ownership and the board of commissioners have no significant effect on tax avoidance, while audit quality partially has a significant effect on tax avoidance. And simultaneously institutional ownership, the board of commissioners and audit quality have a significant effect on tax avoidance.